Do young learners know how to learn a foreign language? - Mihaljević-Djigunović, Jelena (Array, 2001)
A study into young learners’ language learning strategies is described. 23 learners were interviewed in order to find out whether they were aware of what strategies can be useful in learning new vocabulary in English. The data, elicited by means of the projection method, point to the young learners’ awareness of language as well as language learning and teaching processes. The quantitative results of data analysis are taken as indications of possible trends in strategy use that should be looked into in future studies.